Long-term effect of dupilumab on prevention of lung function decline in patients with uncontrolled moderate-to-severe asthma: ATLAS trial design. Issue 2 (6th March 2023) - De Prado Gomez, Lucia; Pavord, Ian; Busse, William; Brightling, Christopher E.; Wechsler, Michael E.; Rabe, Klaus F.; Zhang, Mei; Xing, Jun; Jacob-Nara, Juby A.; Rowe, Paul J.
Background: Many patients with asthma experience loss of lung function over time, and in certain patients this can lead to progressive obstructive patterns similar to COPD. Patients with severe asthma may experience accelerated lung function decline (LFD). However, characteristics and risk factors for LFD in asthma have not been well described. Dupilumab may prevent or slow the rate of LFD in patients with uncontrolled, moderate-to-severe asthma. ATLAS trial is designed to evaluate the role of dupilumab in preventing/slowing LFD over a period of 3 years versus standard-of-care therapy. Methods: ATLAS (clinicaltrials.gov identifier NCT05097287) is a randomised, double-blind, placebo-controlled, multicentre study that will include adult patients with uncontrolled moderate-to-severe asthma. ∼1828 patients will be randomised (2:1) to dupilumab 300 mg or placebo in combination with maintenance therapy every 2 weeks for 3 years. The primary objective is to assess the effect of dupilumab on preventing or slowing LFD by year 1 in the exhaled nitric oxide fraction ( F eNO ) population (patients with F eNO ≥35 ppb). The effect of dupilumab in slowing the rate of LFD by year 2 and year 3 in both F eNO and total populations, exacerbations, asthma control, quality of life, biomarker changes and utility of F eNO as a biomarker of LFD will also be evaluated. Discussion: ATLAS is the first trial assessing the effect of a biologic on LFD, designed to establish the role of dupilumab in prevention of long-term loss of lung function and its potential effect on disease modification, which may provide unique insights into asthma pathophysiology, including predictive and prognostic factors of LFD. The ATLAS trial is designed to establish the role of dupilumab in preventing long-term loss of lung function in patients with moderate-to-severe asthma and its potential effect on disease modification https://bit.ly/3D5BCFQ